Dengue NS1 Antigen: A Tool in Early Detection of Dengue Virus Infection (Journal of Medicine, 2014)
Objectives: This aim of the study was to evaluate the efficacy of NS1 antigen assay for early diagnosis of dengue virus infection in a tertiary care hospital. Methods: This cross sectional study was carried out in medicine unit of Square hospital from May to August 2013. Total 100 patients with dengue fever were included. Complete blood count, alanine aminotransferase (ALT), aspartate aminotransferase (AST), Dengue NS1 antigen and IgM and IgG antibodies of dengue virus were done in all cases. Results: Of the 100 sera tested, 75% were positive for dengue virus infection based on dengue NS1 antigen, IgM antibody and IgG antibody. Dengue NS1 antigen and IgM, IgG antibody were able to detect dengue virus infection between day 1 to day 8 in 92% of samples, 86.7% of samples and 82.6% of samples respectively. Sixty nine percent (69%) were found positive for dengue NS1 antigen, 65% were IgM positive and 62% were IgG positive. Based on the dengue NS1 antigen and IgM antibody combination, 74% were positive for dengue virus infections. Sensitivity of Dengue NS1 antigen was 92.3% and specificity of 74.28% in comparison to IgM antibody. Based on the antigen and IgG antibody combination, detection rate increased to 75%. Sensitivity of dengue NS1 antigen was 90.3% and specificity of 65.8% in comparison to IgG antibody. Conclusion: Dengue NS1 antigen is a useful, sensitive and specific test for early diagnosis of dengue virus infection and it improves diagnostic efficiency in combination with antibody test.DOI: http://dx.doi.org/10.3329/jom.v15i1.19856 J Medicine 2014; 15: 28-30